KORELASI TINGKAT STRES AKADEMIK DENGAN KADAR KOLESTEROL TOTAL MAHASISWA TLM TINGKAT AKHIR UNIVERSITAS ‘AISYIYAH YOGYAKARTA - Azzalia, Diva Calista; Amalia, Arifiani Agustin; Mu’awanah, Isnin Aulia Ulfah (STIKES Insan Cendekia Medika Jombang, 2025)
ABSTRAK Pendahuluan: Mahasiswa tingkat akhir rentan mengalami stres akademik akibat beban tugas akhir dan ujian. Stres kronis dapat memengaruhi fisiologi, termasuk meningkatkan kadar kolesterol. Tujuan : Penelitian ini penting untuk mengetahui hubungan antara tingkat stres akademik dan kadar kolesterol total guna mendukung upaya pencegahan risiko kardiovaskular sejak dini. Metode : Penelitian ini menggunakan desain cross-sectional dengan 36 mahasiswa Teknologi Laboratorium Medis tingkat akhir sebagai sampel. Data dikumpulkan melalui kuesioner Student Life Stress Inventory (SLSI), aktivitas fisik, pola makan, serta pemeriksaan kolesterol total metode Cholesterol Oxidase-Peroxidase Aminoantiphyrine (CHOD-PAP). Analisis dilakukan menggunakan Uji ANOVA dan Uji Korelasi Parsial dengan mengontrol IMT, aktivitas fisik, dan konsumsi makanan tinggi lemak. Hasil : Uji Normalitas menunjukkan data terdistribusi normal. Uji One-Way ANOVA menunjukkan perbedaan signifikan kadar kolesterol total berdasarkan tingkat stres akademik (p 0,001). Uji Post-Hoc LSD menunjukkan perbedaan signifikan antara kelompok tidak stres, stres ringan, dan stres berat. Uji Korelasi Parsial menunjukkan hubungan cukup kuat (r 0,539) setelah mengontrol IMT, aktivitas fisik, dan konsumsi lemak. Kesimpulan : Stres akademik berhubungan signifikan dengan peningkatan kadar kolesterol total pada mahasiswa TLM tingkat akhir. Deteksi dan manajemen stres penting dilakukan sebagai upaya pencegahan risiko gangguan metabolisme lipid dan penyakit kardiovaskular di lingkungan akademik. Kata Kunci: Stres akademik, Kolesterol total, Mahasiswa Teknologi Laboratorium Medis ABSTRACT Introduction: Final-year students are particularly susceptible to academic stress due to the heavy burden of completing final projects, clinical internships, and final examinations. Prolonged or unmanaged academic stress can influence various physiological systems, including lipid metabolism, which may result in elevated cholesterol levels. Such physiological responses are of concern due to their potential contribution to early onset of cardiovascular risk. Objective: This study aimed to examine the relationship between academic stress and total cholesterol levels in final-year students, as part of a preventive strategy for cardiovascular diseases linked to chronic stress. Methods: A cross-sectional study was conducted involving 36 final-year students from the Medical Laboratory Technology Program. Academic stress levels were assessed using the Student Life Stress Inventory (SLSI), while physical activity and dietary fat intake were evaluated using standardized questionnaires. Total cholesterol levels were measured using the Cholesterol Oxidase-Peroxidase Aminoantipyrine (CHOD-PAP) enzymatic method. Statistical analyses included One-Way ANOVA to determine differences across stress levels and Partial Correlation analysis to examine associations while controlling for potential confounding variables such as body mass index (BMI), physical activity, and fat intake. Results: Data distribution was normal. One-Way ANOVA showed statistically significant differences in total cholesterol levels across the three stress level categories (p < 0.001). Post-hoc LSD analysis indicated significant pairwise differences between the no stress, mild stress, and severe stress groups. Partial correlation revealed a moderate positive correlation (r = 0.539) between academic stress and total cholesterol levels, after adjusting for BMI, physical activity, and dietary fat intake. Conclusion: Academic stress is significantly associated with increased total cholesterol levels among final-year students. Early identification and management of academic stress are essential to maintain metabolic health and reduce future cardiovascular disease risk. Keywords: Academic stress, Total cholesterol, Medical Laboratory Technology Students